SUCCESSION IN TEACHING 3D MODELING AND AR/VR TECHNOLOGIES - Tazabekova, P.; Nurbekova, Zh.; Sembayev, T. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
This article is devoted to the continuity in teaching 3D modeling, augmented (AR), and virtual reality (VR) technologies. The authors pay special attention to the integration of these technologies into the educational process, their interrelation, and their importance for the formation of professional skills of future computer science teachers. Topics were considered in two disciplines: “Computer graphics and 3D modeling” and “Augmented and virtual reality”, which have a systematic character and continuity. The project works of students within the framework of studying these disciplines are presented, which were evaluated according to a specially developed assessment scale according to 6 main criteria. The article presents the results of a pedagogical experiment conducted in teaching 3D modeling and AR/VR. 72 students of the educational program “6B01506-Computer Science”, “6B01514-Computer Science-Robotics” and the educational program “6B01505-Physics-Computer Science” took part in the experiment. The phased nature of the study helped to reveal these research questions comprehensively. The phased nature of the study helped to reveal these research questions comprehensively.